The Phase Equilibria of the Al-Co-Er System at 400 and 600℃ - Zhang, Ligang; Zheng, Linghong; Zhao, Fenyan; Liu, Libin; Wang, Dong; Wu, Chenjian (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
The 400℃ and 600℃ isothermal sections of the Al-Co-Er system were studied assisted with X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Electron Probe Micro-Analysis (EPMA) techniques. 18 three-phase fields are identified in the 400℃ isothermal section. The maximum solid solubilities of Al in Co3Er and Co2Er are 13.93 at.% and 16.13 at.%, respectively. Whereas the maximum solid solubilities of Co in Al2Er, Al2Er3 and AlEr2 are 6.93 at.%, 6.65 at.% and 6.49 at.%, respectively. And the solid solution range of λ is 22.22 at.% Al-44.44 at.% Al. While the 600℃ isothermal section includes 20 three-phase fields. The maximum solid solubilities of Al in Co17Er2 and Co7Er2 are 10.17 at.% and 10.24 at.%, respectively. Whereas the maximum solid solubilities of Co in Al2Er and Al2Er3 are 3.63 at.% and 2.01 at.%, respectively.
Keywords: Phase Equilibria; Al-Co-Er; Aluminum alloys